2016
DOI: 10.1177/0267659116667804
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation outcomes in children with hemophagocytic lymphohistiocytosis

Abstract: HLH is an uncommon indication for ECMO and these patients have increased mortality compared to the overall pediatric ECMO population. These data should be factored into decision-making when considering ECMO for pediatric HLH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 18 publications
0
23
2
Order By: Relevance
“…Initiation of ECLS may allow time for immunosuppressive therapies to be effective. A recent study evaluating the survival of pediatric HLH patients on ECLS showed a survival rate of only 30% [94]. This is significantly lower than the general pediatric ECLS survival of 59% but is comparable to other immunocompromised pediatric cohort survival (31%) and neonatal cardiac and E-CPR (extracorporeal cardiopulmonary resuscitation) patients (38%) [94].…”
Section: Intensive Care Presentation and Managementmentioning
confidence: 88%
See 1 more Smart Citation
“…Initiation of ECLS may allow time for immunosuppressive therapies to be effective. A recent study evaluating the survival of pediatric HLH patients on ECLS showed a survival rate of only 30% [94]. This is significantly lower than the general pediatric ECLS survival of 59% but is comparable to other immunocompromised pediatric cohort survival (31%) and neonatal cardiac and E-CPR (extracorporeal cardiopulmonary resuscitation) patients (38%) [94].…”
Section: Intensive Care Presentation and Managementmentioning
confidence: 88%
“…A recent study evaluating the survival of pediatric HLH patients on ECLS showed a survival rate of only 30% [94]. This is significantly lower than the general pediatric ECLS survival of 59% but is comparable to other immunocompromised pediatric cohort survival (31%) and neonatal cardiac and E-CPR (extracorporeal cardiopulmonary resuscitation) patients (38%) [94]. Indication for ECLS included respiratory failure, cardiac failure, and E-CPR with 63% being placed on venoarterial ECLS [94].…”
Section: Intensive Care Presentation and Managementmentioning
confidence: 89%
“…In our patient, ECMO was initiated due to the development of bilateral massive pneumothorax. However, in a recent study on a small cohort of patients, survival of pediatric HLH patients on ECMO was worse than patients without HLH on ECMO ( 37 ). It should be noted that the severity of the clinical manifestations and the high mortality related to the lung involvement may themselves lead to a reduced estimation of the incidence of the lung involvement in FHL, since the patient may die without receiving a genetic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a case series describing 30 pediatric patients with HLH on ECMO, it was demonstrated that pediatric HLH patients on ECMO had worse survival than pediatric patients without HLH on ECMO (27% in HLH patients vs. 63% in non-HLH patients) [ 11 ]. This may be attributed to the fact that ECMO is a potent immunostimulator in and of itself.…”
Section: Discussionmentioning
confidence: 99%